Βίοι Νεομαρτύρων στὸν κώδικα Ξενοφῶντος 25. Πολιτιστικὸ καὶ κοινωνικὸ πλαίσιο. - ΑΝΑΓΝΩΣΤΟΥ ΜΥΡΣΙΝΗ Σ. (Byzantina Symmeikta, 2021)
Lifes of Neomartyrs in Cod . Xenophontos 25. Cultural and Social Framework Research on the neomartyrs of the Orthodox Church has admittedly made significant progress in recent years, with books, studies and articles by older and newer researchers as well as with special conferences that have been organized during the last decades in Greece. The neomartyrs in the hitherto unpublished collection of the codex Xenophontos 25 are a category of saints of our Church dating from the 16th to the 18th century. The purpose of this study is to highlight the social and cultural elements that emerge from the study of their life and martyrdom.